Analisis Bahan Ajar Pembelajaran Kacapi Bani Ambara Pada Mata Pelajaran Seni Budaya Di Sma Negeri 1 Ciamis - Alfin Nurul Azmi; Denden Setiaji; Arni Apriani (Prodi Pendidikan Sendratasik FKIP UMTAS, 2021)
In SMAN 1 Ciamis there is learning Art and Culture in which learning the art of traditional music. Where every student must learn to play a typical musical instrument of West Java, Kacapi. SMAN 1 Ciamis is the only high school in ciamis area that learns traditional musical instruments in learning Art and Culture in the classroom, especially in the practice of playing harp instruments using kacapi kawih. Related to Kacapi's learning in Art and Culture subjects at SMAN 1 Ciamis, researchers are interested in researching how materials and teaching materials are arranged by Art and Culture teachers in order to achieve learning objectives. Because Kacapi learning is rarely taught in other public schools. With the hope that the results of this research can motivate other schools to continue to develop learning in arts and culture subjects and can increase knowledge for the field of art education, especially music arts. This research uses descriptor method with qualitative approach. This research was conducted at SMAN 1 Ciamis located at Jalan Gunung Galuh No. 37, Ciamis District, Ciamis Regency, West Java. The data source used is by conducting observations, interviews, documentation studies and literature studies. Then the data will be analyzed using research deepening analysis techniques with steps to reduce data, present data and draw conclusions. Based on the data analysis conducted, it was concluded that the teaching materials in kacapi kawih learning at SMAN 1 Ciamis are in accordance with the curriculum of high school level. And the teaching material of kacapi kawih learning is a learning module with etude kacapi teaching materials made by art and culture teachers with an adaptation of the simplified Etude kacapi Mang Koko.